Avaliação estética da queiloplastia em indivíduos com fissura labial comparando dois materiais para síntese cutânea - Oliveira, Rosany Larissa Brito de (2018)
Introduction: The nonsyndromic orofacial cleft (OC) is the fourth birth defect and the most common craniofacial malformation. The primary cleft repair surgery in the lip (cheiloplasty) or in the palate (palatoplasty) should be more aesthetic and functional, due to the nose and lip aesthetic side in people with OC has a value which goes beyond the human vanity, it is primordial to the child’s personality formation and his or her relatives. Objective: The objective of this study was to evaluate the cheiloplasty aesthetic results in individuals with unilateral cleft lip, using two different materials for cutaneous synthesis. Methodology: A randomized controlled clinical trial was performed, at the Sociedade Especializada em Atendimento ao Fissurado do Estado de Sergipe (SEAFESE). All subjects who underwent queiloplasty at SEAFESE between October 2014 and June 2017 participated in this study, constituting a population of 50 individuals. The control group had as material for cutaneous synthesis the polyglactin 910 reabsorbable suture and the experimental group had the octyl-2- cyanoacrylate tissue adhesive. These individuals were evaluated by six blinded evaluators with one month and six months post-surgery, at which time standardized frontal face pictures were taken. The esthetical face evaluation was performed using the Visual Analogue Scale (VAS), the Cosmetics Scale Evaluation proposed by Singer and the Classification Scale proposed by Mortier. In addition, an anthropometric analysis proposed by Pietruski was performed. Results: The population sociodemographic profile is an individual with an average age of 3.2 years, with monthly family income below two minimum salaries, most of them are from countryside and have pre-foramen cleft. About the cheiloplasty aesthetic results, in the one-month post-operative follow-up there was no significant statistical difference for VAS and for the Mortier Scale. But in the Singer Scale, the tissue adhesive presented better results for the variables: height, color, hatch marks or suture marks and overall appearance. In the six-month postoperative follow-up, there was no significant statistical difference for VAS as well. However, there was a difference, for the Singer Scale (width, color and hatch marks or suture marks) and in the Mortier Scale (scar and red lip), when better cosmetic results were noticed with the adhesive. In the anthropometric analysis proposed by Pietruski, when the two cutaneous synthesis materials were compared, a significant statistical difference was observed in three of the nineteen parameters evaluated. Finally, about the postoperative complications, there was only one surgical wound partial dehiscence in the control group. Conclusion: The tissue adhesives presented a superior cosmetic result when it was compared to the resorbable sutures. In six-month postoperative follow-up, the adhesive presented superior results in the anthropometric analysis proposed by Pietruski and in the scales proposed by Singer and by Mortier. In the comparison between plastic surgeons and oral and maxillofacial surgeons, there were differences in the evaluations of three variables, when the oral and maxillofacial surgeons were more critical.